Kinetics effects and modeling of mRNA turnover. (1st March 2015) - Palumbo, Maria Concetta; Farina, Lorenzo; Paci, Paola
Abstract : Broader comprehension of gene expression regulatory mechanisms can be gained from a global analysis of how transcription and degradation are coordinated to orchestrate complex cell responses. The role of messenger RNA (mRNA) turnover modulation in gene expression levels has become increasingly recognized. From such perspective, in this review we briefly illustrate how a simple but effective mathematical model of mRNA turnover and some experimental findings, may together shed light on the molecular mechanisms underpinning the major role of mRNA decay rates in shaping the kinetics of gene activation and repression. WIREs RNA 2015, 6:327–336. doi: 10.1002/wrna.1277 This article is categorized under: RNA Turnover and Surveillance > Regulation of RNA Stability